No undocumented child left behind : Plyler v. Doe and the education of undocumented schoolchildren - Olivas, Michael A. (New York : New York University Press, 2016)
This text examines the 1982 U.S. Supreme Court case of Plyler v. Doe. This decision resolved the issue of whether or not state laws could restrict the educational opportunities of immigrant schoolchildren without legal status by denying them permission to enroll or requiring them to pay tuition.
Previously issued in print: 2012.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 12, 2016).
Keywords: Children of illegal aliens -- Education -- Law and legislation -- United States; Law; United States of America, USA; Education; Laws of specific jurisdictions & specific areas of law; Immigration law; Education law